2006
DOI: 10.1152/ajpheart.00153.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac myofibroblasts differentiated in 3D culture exhibit distinct changes in collagen I production, processing, and matrix deposition

Abstract: Myofibroblasts are a differentiated fibroblast cell type characterized by increased contractile capacity and elevated production of extracellular matrix (ECM) proteins. In the heart, myofibroblast expression is implicated in fibrosis associated with pressure-overload hypertrophy, among other pathologies. Although enhanced expression of ECM proteins by myofibroblasts is established, few studies have addressed the nature of the ECM deposited by myofibroblasts. To characterize ECM production and assembly by cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 43 publications
3
49
0
Order By: Relevance
“…Proteins were transferred to nitrocellulose and blocked with 1% casein, and membranes were probed with rabbit anti-mouse collagen I (MD Biosciences). The anti-collagen I antibody recognizes the procollagen ␣1(I) chain with the N-and C-propeptides, the pC-propeptide chain (pC-␣1(I)), and the ␣1(I) chain with both the N-and C-propeptides cleaved (42,43). Membranes were washed with TBS-T (10 mM Tris-HCl, pH 7.6, 100 mM NaCl, and 0.1% Tween 20), probed with appropriate secondary antibody, and developed using Western Lightning MEFs.…”
Section: Methodsmentioning
confidence: 99%
“…Proteins were transferred to nitrocellulose and blocked with 1% casein, and membranes were probed with rabbit anti-mouse collagen I (MD Biosciences). The anti-collagen I antibody recognizes the procollagen ␣1(I) chain with the N-and C-propeptides, the pC-propeptide chain (pC-␣1(I)), and the ␣1(I) chain with both the N-and C-propeptides cleaved (42,43). Membranes were washed with TBS-T (10 mM Tris-HCl, pH 7.6, 100 mM NaCl, and 0.1% Tween 20), probed with appropriate secondary antibody, and developed using Western Lightning MEFs.…”
Section: Methodsmentioning
confidence: 99%
“…1 Differentiation of cardiac fibroblasts into myofibroblasts is critical to the production and deposition of collagens and plays a decisive role in myocardial fibrosis and morphological alterations during the progression of adaptive myocardial hypertrophy to decompensation and heart failure. 1,2 Among the plethora of identified fibrogenic factors, transforming growth factor (TGF)-␤ 3 plays a fundamental role in hypertrophic and fibrotic remodeling of the heart, where it regulates cardiomyocyte growth, fibroblast activation, and ECM deposition. 4,5 The expression of ventricular TGF-␤ mRNA and protein is increased in numerous models of pathological cardiac hypertrophy and in cardiac cells in response to putative hypertrophic stimuli.…”
Section: A Key Antifibrogenic Mechanism Of Atrial Natriuretic Peptidementioning
confidence: 99%
“…Besides influencing cellular behavior based on specific molecular signaling, dimensionality and biomechanical cues in the lung clearly impact the effect of ECM on interstitial cell phenotype (8)(9)(10)(11)(12)(13)(14)(15). Although traditional in vitro studies of cell-matrix interactions usually rely on matrix-coated culture dishes, these artificial environments do not truly recapitulate the in vivo conditions under which cells reside.…”
mentioning
confidence: 99%
“…In stark contrast, cells within the normal three-dimensional microenvironment of the lung extend membrane protrusions in all dimensions; for example, alveolar type I cells reach through pores of Kohn, and fibroblasts extend to contact endothelial cells and type I cells in numerous alveolar spaces to "sample" multiple alveoli simultaneously (16). Studies have also shown that phenotypic behavior depends on the position of the cell in space, with quite disparate phenotypes observed between fibroblasts in two-dimensional, compared with three-dimensional, environments (8)(9)(10).…”
mentioning
confidence: 99%